2023
DOI: 10.3390/cancers15041022
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Therapeutic Opportunities in the dMMR/MSI-H Colorectal Cancer Landscape

Abstract: About 5 to 15% of all colorectal cancers harbor mismatch repair deficient/microsatellite instability–high status (dMMR/MSI-H) that associates with high tumor mutation burden and increased immunogenicity. As a result, and in contrast to other colorectal cancer phenotypes, a significant subset of dMMR/MSI-H cancer patients strongly benefit from immunotherapy. Yet, a large proportion of these tumors remain unresponsive to any immuno-modulating treatment. For this reason, current efforts are focused on the charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 143 publications
0
11
0
Order By: Relevance
“…Our study found that 6.3% of all rectal cancer patients were MSI-H. While MSI-H tumors account for 5–15% of all colorectal cancers [ 13 ], it has been previously shown that MSI-H rectal cancers are more infrequent than MSI-H colon cancer and may account for as low as 2% of all rectal cancers [ 14 ]. The present study found that early-onset patients had more advanced disease, received more systemic and radiation treatment, and had longer OS than late-onset tumors.…”
Section: Discussionmentioning
confidence: 55%
“…Our study found that 6.3% of all rectal cancer patients were MSI-H. While MSI-H tumors account for 5–15% of all colorectal cancers [ 13 ], it has been previously shown that MSI-H rectal cancers are more infrequent than MSI-H colon cancer and may account for as low as 2% of all rectal cancers [ 14 ]. The present study found that early-onset patients had more advanced disease, received more systemic and radiation treatment, and had longer OS than late-onset tumors.…”
Section: Discussionmentioning
confidence: 55%
“…Consequently, MSI is among the most promising markers being studied. It has predictive value since, according to most studies, MSI‐H was associated with a better prognosis 19,20 …”
Section: Tissue‐based Biomarkersmentioning
confidence: 99%
“…It has predictive value since, according to most studies, MSI-H was associated with a better prognosis. 19,20 Yet it is still unclear if this phenomenon results from the fact that MSI-H cancers are less aggressive by nature or tolerate chemotherapy better. Chemotherapy options currently include monotherapy, mainly Fluorouracil (5-FU), and combination therapy, which includes one or more medications such as irinotecan and Oxaliplatin (OX).…”
Section: Microsatellite Instability (Msi) As a Prognostic Factormentioning
confidence: 99%
“…Approximately 15% of all CRCs exhibit MSI-H or dMMR characteristics[ 160 ]. Patients with MSI-H or dMMR tumors before ICIs therapy continue to have a poor prognosis.…”
Section: Immune Profiling Of Msi and Mss Crc Influence Icis Successmentioning
confidence: 99%